2021
DOI: 10.1002/eat.23590
|View full text |Cite
|
Sign up to set email alerts
|

Change in eating‐disorder psychopathology network structure in patients with anorexia nervosa treated with intensive cognitive behavior therapy

Abstract: Objective: This study was designed to compare the change in eating-disorder feature networks in patients with anorexia nervosa after treatment with intensive enhanced cognitive behavior therapy (CBT-E).Methods: Patients seeking treatment for anorexia nervosa were consecutively recruited from January 2016 to September 2020. All patients aged ≥16 years who completed a 20-week intensive CBT-E program (13 weeks of inpatient followed by 7 weeks of day-hospital treatment) were included in the study. Body mass index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 48 publications
3
42
0
1
Order By: Relevance
“…assessment of treatment outcome (Calugi et al, 2021; Elliott et al, 2020; Hagan et al, 2021; Hilbert et al, 2020; Olatunji et al, 2018; Smith et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…assessment of treatment outcome (Calugi et al, 2021; Elliott et al, 2020; Hagan et al, 2021; Hilbert et al, 2020; Olatunji et al, 2018; Smith et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, results about these metrics should be interpreted with care. As an additional proof about this fact, many articles reported betweenness and closeness centrality as not satisfying the minimum stability results and did not include their estimation in the network description (Aloi et al, 2021; Calugi et al, 2021; Forrest et al, 2018; Monteleone et al, 2020; Rodgers et al, 2018; Smith et al, 2019; Vanzhula et al, 2019). Others decided instead to take these measures into account but did not assess their stability (Forbush et al, 2016; Olatunji et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it can be concluded that, in this case, the cognitive–behavioural approach was successful in treating a case of anorexia nervosa, which is consistent with other findings in different areas, such as hospitals [ 19 ]. However, this approach has not always received the same support in scientific literature [ 6 ], despite it also being true that attempts have been made to discover enriched variations of this therapy [ 20 ] in pursuit of a more efficient type of therapy. This has been the case with enhanced cognitive behaviour therapy, of which insufficient studies exist at present to determine its efficacy, though the results obtained thus far have shown promise [ 21 ].…”
Section: Discussionmentioning
confidence: 99%